2019
DOI: 10.2144/fsoa-2019-0079
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors for Patients Treated With Abiraterone

Abstract: Aim: To evaluate prostate-specific antigen response (PSAr) defined as a ≥50% decrease in PSA concentration from the pretreatment value, as a prognostic factor in patients with metastatic castration-resistant prostate cancer (mCRPC) treated with abiraterone acetate (AA). Methods: Retrospective evaluation of patients with mCRPC treated with AA. Results: 124 patients were identified. Median overall survival and progression-free survival for patients achieving PSAr versus patients without PSAr were 29.3 versus 9.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
1
4
0
1
Order By: Relevance
“…To date, PSA is the only biochemical marker that has proved useful in the follow-up of patients with prostate cancer. In the context of mCRPC, some studies reported that patients who achieved a PSA decline of ≥50% from baseline had a longer survival compared with those who did not 19 27–30. Our findings are in accordance with previous studies, showing a correlation between PSA response and OS.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…To date, PSA is the only biochemical marker that has proved useful in the follow-up of patients with prostate cancer. In the context of mCRPC, some studies reported that patients who achieved a PSA decline of ≥50% from baseline had a longer survival compared with those who did not 19 27–30. Our findings are in accordance with previous studies, showing a correlation between PSA response and OS.…”
Section: Discussionsupporting
confidence: 92%
“…It is well established that some clinical variables are related to a worse prognosis in mCRCP15–18: elevated baseline prostate specific antigen (PSA), Gleason score >8, poor performance status, elevated levels of alkaline phosphatase (ALP), presence of anaemia, large extent of disease (number and location of metastases) and the presence of pain are associated with shorter survival. Also, patients with a biochemical response, defined as a reduction in PSA of at least 50% from baseline during treatment, have an improved survival 19…”
Section: Introductionmentioning
confidence: 99%
“…In fact, AA has demonstrated activity in mCRPC regardless of patient age, 5 and several studies have found that Gleason score may well lose prognostic impact in heavily pretreated mCRPC patients. 13 , 17 19 Additionally, the number of prior chemotherapy lines was not associated with OS. More than 50% of our patients who had received a second line of chemotherapy before AA were treated with docetaxel, in accordance with common practice at that time, and the interval between ending docetaxel and starting AA was more highly associated with OS than the number of previous lines.…”
Section: Discussionmentioning
confidence: 92%
“…Treatment with abiraterone acetate demonstrated that PSA reduction > 30% or ≥ 50% remained predictive of better PFS and OS [63,64]. Duration of treatment > 3 months by abiraterone acetate was significantly predictor (p = 0.00025) of treatment [65].…”
Section: Psa and Psa Kineticsmentioning
confidence: 96%